Legal Protection For Employees Who Are Harmed By Data Misuse By The Company - M. Alfitra Gita Armanda; Krisnadi Nasution (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
The purpose of this study is to find out how to protect the law for employees who are harmed by the misuse of personal data by the company. This study uses a type of normative juridical research using a statutory approach and a conceptual approach. The development of the times that has led to the development of technology and information systems has caused a lot of data misuse by the public. Companies, in their day-to-day operations, collect and process employee data for a variety of purposes, from personnel administration, performance appraisals, to strategic planning. However, the use of this data often poses a risk of misuse. Misuse of data can take many forms, including but not limited to unauthorized disclosure of personal data, use of data for unauthorized purposes, and disregard for adequate security measures. Misuse of data by companies can take many forms, such as unauthorized dissemination of personal information, use of data for unauthorized purposes, or neglect of data security that leads to leaks. The consequences of this abuse can include financial losses, reputational damage, and psychological impacts for affected employees. The results of this study show that the legal steps that can be taken by employees in dealing with data breaches or misuse reflect the importance of legal protection in safeguarding individual rights. By providing a channel for employees to report violations and sue for damages, the law creates a mechanism that encourages companies to take responsibility and maintain the privacy of employee data.